A Clinical Study of the Intra-Neuroendoscopic Technique for the Treatment of Subacute-Chronic and Chronic Septal Subdural Hematoma - Du, Bo; Xu, Jianzhong; Hu, Jintao; Zhong, Xianliang; Liang, Jian; Lei, Pengfei; Wang, Hao; Li, Weichun; Peng, Yuping; Shan, Aijun; Zhang, Yujuan (Frontiers in Neurology, 2020)
Objective: The surgical technique, safety, efficacy, and clinical application value of the intra-neuroendoscopic technique (INET) for the treatment of subacute-chronic and chronic septal subdural hematoma was investigated based on the structure and pathological features of the hematoma wall, and the critical factors of hematoma growth and recurrence were determined, in order to provide reference for clinical drug treatment. Methods: This was non-randomized concurrent control study. A total of 94 patients who met the inclusion criteria were recruited between May 2015 and February 2019 and were divided into the INET treatment group (INET group, 45 cases) and the burr hole drainage (BHD) treatment group (control group, 49 cases). The hematoma fluid components and the morphological structure and pathological characteristics of the hematoma wall were analyzed, and the surgical duration, subdural drainage tube (SDT) placement duration, intracranial infection rate, Bender grade at the 1 month post-operative follow-up and hematoma recurrence rate within the 6 months of post-operative follow-up were compared between the two groups. A multiple logistic regression model was established to analyze the risk factors associated with recurrence within 6 months. Results: Intraoperative endoscopy showed that the adhesion bands that formed early in the hematoma cavity were strip-like and that those that formed late were lock-column-like. The hematoma cavity was divided into different-sized chambers with by these strips/columns. Pathological sections of cyst wall reveled angiogenesis inside the cyst and mucus-like changes, rupture and hemorrhage in the vascular wall. Obvious inflammatory cell infiltration and fibrous connective tissue hyperplasia were observed in the cyst wall. The osmotic pressure of the hematoma fluid was not significantly different from that of the peripheral venous blood [(296.7 ± 10.3) mOsm/kg vs. (291.5 ± 12.4) mOsm/kg, p = 0.68]. However, the D-dimer contents which reflect the severity of fibrinolysis in the hematoma and the proinflammatory cytokine interleukin 6 (IL-6) were significantly higher in the hematoma fluid than in the peripheral venous blood. The surgery duration for the INET group was significantly longer than that for the control group [(60.4 ± 10.6) min vs. (44.1 ± 9.8) min, p = 0.00], but both the hematoma recurrence rate within 6 months of post-operative follow-up (4.4 vs. 24.5%, p = 0.00) and the SDT placement duration [(2.1 ± 0.6) d vs. (3.9 ± 0.7) d, p = 0.00] for the INET group were both lower than those for the control group. The intracranial infection rate did not differ significantly between the two groups (4.4 vs. 10.2%, p = 0.50). The overall effective rate of the Bender grade at 1 month of follow-up did not differ significantly between the two groups (95.6 vs. 87.8%, p = 0.32), but the proportion of patients who recovered to Bender grade 0 with no symptoms was significantly higher in the INET group than in the control group (86.7 vs. 67.3%, p = 0.03). Multiple logistic regression analysis showed that INET surgery [odds ratio (OR) 3.71, 95% confidence interval (CI) 1.31–9.62, p = 0.02], age of 65 years or younger (OR 1.51, 95% CI 1.05–2.87, p = 0.03) and unilateral subdural hematoma (OR 1.76, 95% CI 1.05–3.41, p = 0.02) were independent factors that reduced the post-operative recurrence rate. Conclusion: The INET surgical plan based on the structure and pathological features of the subacute-chronic and chronic subdural hematoma wall can reduce the recurrence rate and improve the clinical prognosis. Trial registration:ClinicalTrials.gov, NCT02515903. Registered 5 August, 2015.